2018
DOI: 10.1002/joc.5843
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impacts of the Pacific Ocean sea surface temperature anomalies on a drought event in southwestern China with a piecewise‐integration method

Abstract: Model-based sensitivity experiments are a widely used method for studying climate change attributions. In traditional climate sensitivity studies, "climate drift" occurs because of the accumulation of model errors during long-term integrations, both in "actual" and "hypothetical" states. A more accurate piecewise-integration method is used to reduce the model errors, dividing the continuous simulation into a series of sequential short-term simulations. The model fields are updated at the end of each subinterva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, the causes of the anomalous Indian monsoon and EB is still unclear. Previous studies recognized that the tropical Pacific SSTA is an important factor in anomalous atmospheric circulation [55,56]. As the third year of a rare triple La Niña, the cold SST anomaly in the Equatorial Eastern Pacific is developed in the summer of 2022.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes of the anomalous Indian monsoon and EB is still unclear. Previous studies recognized that the tropical Pacific SSTA is an important factor in anomalous atmospheric circulation [55,56]. As the third year of a rare triple La Niña, the cold SST anomaly in the Equatorial Eastern Pacific is developed in the summer of 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The PWI has been proved to be effective in reducing the simulation errors (Gan et al 2019;Shao et al 2015;Zhang et al 2008). In the following section, a complex climate model is used to test the simulations of GHGs-induced global climate change using both the CONT and the PWI.…”
Section: The Pwi Approachmentioning
confidence: 99%
“…Against the background of global climate change and the increasing intensity of human activities, many scholars have considered various methods to study the attribution of drought, and have achieved substantive results. Gan used the continuous integral method and piecewise integral method to attribute drought events in Southwest China from 2009 to 2010 [20]. The experiment revealed that insufficient precipitation and high temperatures are the main driving forces of the formation and maintenance of drought.…”
Section: Introductionmentioning
confidence: 99%